Titan's ionosphere: A survey of solar EUV influences. Issue 7 (3rd July 2017) - Shebanits, O.; Vigren, E.; Wahlund, J.‐E.; Holmberg, M. K. G.; Morooka, M.; Edberg, N. J. T.; Mandt, K. E.; Waite, J. H.
Abstract: Effects of solar EUV on positive ions and heavy negative charge carriers (molecular ions, aerosol, and/or dust) in Titan's ionosphere are studied over the course of almost 12 years, including 78 flybys below 1400 km altitude between TA (October 2004) and T120 (June 2016). The Radio and Plasma Wave Science/Langmuir Probe‐measured ion charge densities (normalized by the solar zenith angle) show statistically significant variations with respect to the solar EUV flux. Dayside charge densities increase by a factor of ≈2 from solar minimum to maximum, while nightside charge densities are found to anticorrelate with the EUV flux and decrease by a factor of ≈3–4. The overall EUV dependence of the ion charge densities suggest inapplicability of the idealized Chapman theory below 1200 km in Titan's ionosphere. Nightside charge densities are also found to vary along Titan's orbit, with higher values in the sunward magnetosphere of Saturn compared to the magnetotail. Key Points: Ion and dust grain charge densities near the ionospheric peak enhanced while the peak altitudes are decreased by higher solar EUV flux Ionospheric nightside charge densities decrease with higher solar EUV flux Chapman theory not applicable for Titan's (dayside) ionosphere below 1200 km altitude Plain Language Summary: Satun's moon Titan hosts a fully developed atmosphere of nitrogen and methane extending up to almost an entire Titan radius above the surface. The top atmosphere is ionized primarily by the solar radiation on the dayside and energetic particles on the nightside, initiating a complex organic chemistry. Effects of solar radiation on Titan's ionosphere are studied over the course of almost 12 years, (October 2004 to June 2016). The dayside ionospheric plasma densities (ions and charged dust grains) cannot be described by the Chapman theory. On the nightside, the plasma densities anticorrelate with the solar radiation flux, possibly due to photochemistry of the upper atmosphere being altered by the higher flux. Nightside plasma densities are also found to vary along Titan's orbit, with higher values in the sunward magnetosphere of Saturn compared to the magnetotail.